Factors Influencing the Planning of Production Activities in Agricultures - Hafizov Bunyodjon Zayniddin o’g’li (Zien Journals, 2021)
This article presents external and internal factors, direct and indirect factors that directly affect the process of production of agricultural clusters.
Keywords: External factors; internal factors; direct factors; indirect factors